Confucianism and Catholicism : reinvigorating the dialogue - Slater, Michael R., 1976-; Cline, Erin M.; Ivanhoe, Philip J., 1954- (University of Notre Dame Press, 2020)
"Confucianism and Catholicism are among the most influential religious traditions and share a long and intricate relationship. Beginning with the work of Matteo Ricci (1552-1610), the nature of this relationship has sometimes generated great debate, which is still alive today. The ten essays in this volume continue and advance this long conversation. Written by specialists in both traditions, the essays are organized into two groups. Those in the first group focus primarily on the historical and cultural contexts in which Confucianism and Catholicism encountered one another in the four major Confucian cultures of East Asia (China, Vietnam, Korea, and Japan). These essays seek to understand specific figures, texts, and issues in light of those broader contexts. The essays in the second part offer comparative and constructive studies of specific figures, texts, and issues in the Confucian and Catholic traditions from both theological and philosophical perspectives. By bringing these historical and constructive perspectives together, this volume seeks not only to understand the past dialogue between these traditions, but also to renew and reinvigorate the conversation between them today. In light of the unprecedented expansion of Eastern Asian influence in recent decades, and considering the myriad of challenges and new opportunities faced by both the Confucian and Catholic traditions in a world that is rapidly becoming globalized, this volume could not be more timely. Confucianism and Catholicism: Reinvigorating the Dialogue will be of interest to professional theologians, historians, and scholars of religion, as well as those who work in interreligious dialogue"--